Pendekatan Ekosistem pada Pengelolaan Perikanan Lemuru Skala Besar Melalui Penilaian Domain Teknik Penangkapan Ikan di Perairan Selat Bali - Arip, Arip; Restu, I Wayan; Pratiwi, Made Ayu (Current Trends in Aquatic Science, 2023)
Fishery activities  Sardinella lemuru  in the waters of the Bali Strait are the largest source of economy for fishermen in Pengambengan, Jembrana Regency, Bali. The purpose of this study was to determine the condition of the lemuru fishery in the Pengambengan Fishing Port by assessing the domain of fishing techniques in fisheries management using an ecosystem approach (EAFM). The results of the assessment of the indicators of destructive and/or illegal fishing methods get a score of 3, the indicator of modification and fishing aids gets a score of 1, the indicator of fishing capacity and fishing effort gets a score of 3, the selectivity of fishing gets a score of 3, the suitability of functions and the size of the vessel according to legal documents get a score of 1 and fishing boat crew certification following regulations gets a score of 1. Based on the results of the composite score, the value obtained is 73.33 which means that the lemuru fishery in Pengambengan Fishing Port based on the fishing technique domain is good with a colored flag model light green.